2021
DOI: 10.1007/s00477-020-01954-2
|View full text |Cite
|
Sign up to set email alerts
|

Choosing between Gaussian and MPS simulation: the role of data information content—a case study using uncertain interpretation data points

Abstract: Integration of geophysical data with information such as from boreholes and expert domain knowledge is often performed as cognitive or explicit geological modeling when generating deterministic geological models of the subsurface. However, such cognitive geological models lack the ability to express the uncertainty of layer boundaries. To remedy the shortcomings of this strategy we propose a novel stochastic methodology combining the efforts of probabilistic data integration and cognitive modeling. We treat ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…If some geologically relevant points are available from for example borehole information, it is trivial to include these in the draw by setting the draw probability in the PM to 1. Madsen et al (2021b) suggest using the gradient as a measure to calculate the points that are most relevant for describing the surface. As was the case for the Laplacians, the user would look for areas with a steep gradient.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 2 more Smart Citations
“…If some geologically relevant points are available from for example borehole information, it is trivial to include these in the draw by setting the draw probability in the PM to 1. Madsen et al (2021b) suggest using the gradient as a measure to calculate the points that are most relevant for describing the surface. As was the case for the Laplacians, the user would look for areas with a steep gradient.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Agrawal et al 2006;Boissonnat & Oudot 2006;Harker & O'Leary 2015). However, to our knowledge no method or algorithm is currently available that considers the spatial properties of the surface when sampling points from a (geological) surface, although Hansen (2021) and Madsen et al (2021b) showed that information content differs between points. Thus, the selection of points matters in terms of recreating the essential features of the surface.…”
Section: Potential Application(s) For This Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These realizations are generated using stochastic modeling that accounts for the spatial dependency between the model parameters. We choose MPS simulation over, e.g., a two-point geostatistical approach because it is generally more capable of producing realizations with geological realism in terms of correlation and coherency of geological features (Journel and Zhang, 2006;Madsen et al, 2021;Mariethoz and Caers, 2015). Effectively reproducing coherent layers is key for successful subsequent hydrological modeling.…”
Section: Mps Modelingmentioning
confidence: 99%
“…Both MPS and SGAN methods typically rely on training images as a source of nonstationary spatial statistical information. As noted in literature (Mariethoz, 2018;Madsen et al, 2021), these methods are most effective in when there is a severe scarcity or abundance of information present; however, they may not perform optimally in cases where an intermediate level of geological detail from secondary information such as geophysical data is available, which is the issue addressed in this study.…”
Section: Introductionmentioning
confidence: 99%